2021
DOI: 10.1111/ejh.13586
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of ixazomib/lenalidomide/dexamethasone for multiple myeloma: A multicenter retrospective analysis

Abstract: Objectives This study aimed to investigate real‐world data of ixazomib plus lenalidomide and dexamethasone (IRd) therapy for patients with relapsed and refractory multiple myeloma (RRMM). Methods We retrospectively analyzed 122 patients treated with IRd at 16 centers from May 2017 to January 2019 by using the Kansai Myeloma Forum database. Result At the start of IRd, the median age was 72 years, 66.7% of patients had IgG type, and the median number of prior therapies was 4, comprising bortezomib (85.4%) and le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
(38 reference statements)
0
4
0
1
Order By: Relevance
“…Median PFS was 11.9 months while median OS was not reached. IRd regimen showed poor efficacy, especially in patients without the IgG M-protein component and refractory to lenalidomide [41].…”
Section: Discussionmentioning
confidence: 98%
“…Median PFS was 11.9 months while median OS was not reached. IRd regimen showed poor efficacy, especially in patients without the IgG M-protein component and refractory to lenalidomide [41].…”
Section: Discussionmentioning
confidence: 98%
“…Shorter mPFS were reported in Hungarian study, possibly due to more heavily pretreated patients and LEN supply issues, similarly the Canadian MCRN analysis and Chinese real-world analysis reported shorter mPFS, possibly due to lenalidomide or bortezomib pretreatment and due to inclusion of other ixazomib based therapies [ 24 , 25 , 26 ]. Similarly, in the retrospective analysis by Takakuwa et al, the outcomes of IRD were not favorable, probably due to previous pretreatment (with median of four prior therapies) including lenalidomide and bortezomib [ 27 ]. On the other hand, the Slovak data from routine practice demonstrated very long PFS of 43 months [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In another study [17] , 90 RRMM patients who received eight cycles of IRD were observed; the results showed that the total effective rate was 51.1%; 23.3% reached CR or VGPR, 10% reached MR, and the clinical benefit rate was 61.1%; the effective rate, PFS, and overall survival (OS) were similar in patients with or without t(4;14) and/or del(17p); however, the PFS and OS were significantly shortened in patients with 1q21 gain; multiple regression analysis showed that the gain of 1q21 is the most critical factor related to OS [17] . A multicenter retrospective analysis showed that the PFS and OS of IgG patients were significantly better than those of non-IgG patients [18] . In this study, among the 20 patients, one patient achieved CR, four patients achieved VGPR, and seven patients achieved PR; the ORR was 60.00%, and 25.00% achieved VGPR or more; 14 patients continued to receive ixazomib treatment, five patients received other treatment regimen due to disease progression, and one patient died due to multiple organ failure.…”
Section: Discussionmentioning
confidence: 99%